2015
DOI: 10.1108/et-09-2013-0115
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of factors that affect the research progress of international PhD students from the Middle East

Abstract: Purpose -Despite the critical issues involving Middle East countries such as war and a drop in currency exchange rates, a large number of students leave their country to pursue a higher education abroad, every year. The purpose of this paper is to understand the difficulties that these students face while conducting their research in a foreign country and in doing so hopes to enhance a greater awareness of the kind of hindrances they face to complete their studies. Design/methodology/approach -The respondents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…As people age, they acquire more responsibilities and family obligations; thus, older PhD students likely experience more severe time and resource constraints, which can require them to split their time and resources to cover family, social and employment obligations, in addition to their studies. The finding that younger PhD students (under 40 years) receive significantly more financial support also could explain their faster pace, because financial constraints can influence PhD students' progress and success (Bair & Haworth, 2004;Groen et al, 2008;Jiranek, 2010;Khozaei et al, 2015;Mohamed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As people age, they acquire more responsibilities and family obligations; thus, older PhD students likely experience more severe time and resource constraints, which can require them to split their time and resources to cover family, social and employment obligations, in addition to their studies. The finding that younger PhD students (under 40 years) receive significantly more financial support also could explain their faster pace, because financial constraints can influence PhD students' progress and success (Bair & Haworth, 2004;Groen et al, 2008;Jiranek, 2010;Khozaei et al, 2015;Mohamed et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Employment status is sometimes related to the availability and adequacy of financial aid and family commitments. For example, PhD students who must work while studying have difficulty finalising their PhD projects (Bair & Haworth, 2004;Ho, Wong & Wong, 2010;Khozaei, Khozaei & Salleh, 2015;Wao & Onwuegbuzie, 2011). Students working outside their university and in jobs unrelated to their PhD research area also progress more slowly than those who work in a research project related to their PhD work (Bair & Haworth, 2004;Herman, 2011;Wao & Onwuegbuzie, 2011).…”
Section: Background Characteristicsmentioning
confidence: 99%
“…Other literature commonly relates supervision issues to a supervisor's busy schedule (Abiddin & West, 2007), the differing levels of expectation between the supervisor and students (Ismail & Abiddin, 2009), communication issues (Ismail et al, 2013) and lack of clear guidance and feedback (Wang & Li, 2008). International postgradaute students in Khozaei et al's (2015) study also stated that repeated harsh feedback received from supervisors hampered their research growth and contributed to their low confidence levels. When these supervision issues reach severe levels, supervision ethical issues enter the discussion.…”
Section: Introductionmentioning
confidence: 94%
“…As such, supervision ethical issues are seen as dereliction of a supervisor's responsibility towards supervisees . For instance, Middle Eastern postgraduate students studying in one South East Asian university experienced research hindrance due to the supervisor's unavailability and the lack of commitment shown towards assisting students (Khozaei et al, 2015). Davis (2019) further posits that a supervisor's hectic roster impacts on students negatively, "leading to discomfort, loss of self-esteem and finally, all too often, peril" (p. 454).…”
Section: Introductionmentioning
confidence: 99%
“…It can be inferred that a similar challenge could be faced by postgraduate students in the Malaysian context. A study of postgraduate Arab students in Malaysia found that poor writing skills and unfamiliarity with grammar affected students' ability to present ideas and concepts in a lucid and coherent manner; these obstacles eventually affected their research progress (Khozaei et al 2015). Li and Vandermensbrugghe (2011) highlight that some of difficulties that NESB students face are the capacity to write with clarity and confidence in English, develop an understanding of the conventions of academic writing practices in their disciplines, and recognise the institutional expectations and standards of thesis writing at their degree level.…”
Section: Research Writing Problems and Responsesmentioning
confidence: 99%